Maternal L-proline supplementation enhances fetal survival, placental development, and nutrient transport in mice†. Issue 4 (10th November 2018) - Liu, Ning; Dai, Zhaolai; Zhang, Yunchang; Chen, Jingqing; Yang, Ying; Wu, Guoyao; Tso, Patrick; Wu, Zhenlong
Abstract: L-Proline (proline) in amniotic fluid was markedly increased during pregnancy in both pigs and sheep. However, in vivo data to support a beneficial effect of proline on fetal survival are not available. In this study, pregnant C57BL/6J mice were fed a purified diet supplemented with or without 0.50% proline from embryonic day 0.5 (E0.5) to E12.5 or term. Results indicated that dietary supplementation with proline to gestating mice enhanced fetal survival, reproductive performance, the concentrations of proline, arginine, aspartic acid, and tryptophan in plasma and amniotic fluid, while decreasing the concentrations of ammonia and urea in plasma and amniotic fluid. Placental mRNA levels for amino acid transporters, including Slc36a4, Slc38a2, Slc38a4, Slc6a14, and Na + /K + ATPase subunit-1α ( Atp1a1 ), fatty acid transporter Slc27a4, and glucose transporters Slc2a1 and S lc2a3, were augmented in proline-supplemented mice, compared with the control group. Histological analysis showed that proline supplementation enhanced labyrinth zone in the placenta of mice at E12.5, mRNA levels for Vegf, Vegfr, Nos2, and Nos3, compared with the controls. Western blot analysis showed that proline supplementation increased protein abundances of phosphorylated (p)-mTORC1, p-ribosomal protein S6 kinase (p70S6K), and p-eukaryotic translation initiation factor 4E-binding protein 1 (4E-BP1), as well as the protein level of GCN2 (a negative regulator of mTORC1 signaling). Collectively, our results indicate a novel functional role of proline in improving placental development and fetal survival by enhancing placental nutrient transport, angiogenesis, and protein synthesis. Abstract : Proline supplementation enhances placental nutrient transport, angiogenesis, and protein synthesis, which are critical for fetal survival in mice.